2018
DOI: 10.1071/an16746
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical changes of semimembranosus muscle during the processing of dry-cured ham from Celta pig. Effect of crossbreeding with Duroc and Landrace genotypes

Abstract: Physicochemical characteristics of dry-cured hams from three genetic types, Celta breed (C line), Celta × Duroc (C × D) and Celta × Landrace (C × L) were determined on the semimembranosus muscle during 551 days of aging. Hams were obtained from 60 pigs reared in extensive systems and finished with a commercial feeding. Physicochemical parameters (pH and water activity) and chemical composition, (moisture, intramuscular fat, ash, protein and total chlorides content), colour parameters (L*, a* and b*) and lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
11
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 40 publications
15
11
3
Order By: Relevance
“…Then again, collagen is also a compound that has been related to the hardness of meat, but previous studies have shown that, in the case of pork meat, it showed low correlation coefficients with tenderness [ 43 ]. The outcomes obtained for the shear force in our research ( Table 2 ) were slightly higher than those obtained by other researchers [ 44 , 45 , 46 ] in the Longissimus pig muscle, since the shear force determined by them was between 32 and 49 N. Moreover, the values found in the present research were also higher than those described in the raw Biceps femoris muscle (about 18 N) from Celta pig [ 33 ]. This fact was expected, since raw meat is not comparable to cooked meat.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…Then again, collagen is also a compound that has been related to the hardness of meat, but previous studies have shown that, in the case of pork meat, it showed low correlation coefficients with tenderness [ 43 ]. The outcomes obtained for the shear force in our research ( Table 2 ) were slightly higher than those obtained by other researchers [ 44 , 45 , 46 ] in the Longissimus pig muscle, since the shear force determined by them was between 32 and 49 N. Moreover, the values found in the present research were also higher than those described in the raw Biceps femoris muscle (about 18 N) from Celta pig [ 33 ]. This fact was expected, since raw meat is not comparable to cooked meat.…”
Section: Resultscontrasting
confidence: 86%
“…In relation to the value of redness (a*), there was a decrease in this parameter in all culinary treatments with respect to uncooked Biceps femoris muscle, where an a* value of 18.1 was found [ 33 ]. More specifically, frying was the method that provided the highest value for both diets (9.34 for CH and 10.32 for CF slices) followed by roasted (7.15 and 7.52 for CH and CF slices, respectively), grilled (6.31 for CH and 6.39 for CF samples) and microwaved (5.89 and 6.34 for CH and CF samples, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFA: Saturated fatty acids; MUFA: Monounsaturated fatty acids; PUFA: Polyunsaturated fatty acids; Data were obtained from [75,76,77,78,79,80,81]. …”
Section: Figurementioning
confidence: 99%
“…However, there are no studies conducted with deer meat. Taking into account that genetic factors influence enzymatic activities and that the meat composition influence the biochemical changes produced during the different stages of dry‐cured meat process (Bermúdez et al ., ), the results obtained in this research will provide us with information about the possibility of using deer meat for the preparation of dry‐cured loin. In this context, venison meat is characterised by low fat and cholesterol contents and high levels of protein, essential amino acids, essential and long‐chain polyunsaturated fatty acids and iron (Lorenzo et al ., ; Maggiolino et al ., ; Serrano et al ., ).…”
Section: Introductionmentioning
confidence: 99%